STEEL SEMIRIGID STRUCTURES ENERGY STATE UNDER SEISMIC ACTIONS - Moldovan, Silviu-Marius (International Journal of Research -GRANTHAALAYAH, 2022)
Intended contribution proposes an energy-based approach to the assessment of capability of semirigid multi-storey steel structures to dissipate seismically induced energy via semirigidly connecting zones of the structure. The energy state of multi-storey structure is defined in terms of the energy balance equation. Total amount of seismically induced energy is divided into its classic components: kinetic energy, strain energy and dissipated energy. Dissipated energy is - in its turn - split into the amount dissipated by the structure itself (Eds) and the amount dissipated by the semirigidly connected zones (Edc). The last is computed as the equivalent of work performed by the bending moments associated to the semirigid connections through the relative rotations of the connections. Proposed procedure is further illustrated by several dynamic / seismical analyses of one multi-storey steel structure subjected to two reference earthquakes. Beam to column semirigid connections is of top - and seat - angle with double web-angles (TSDW) make up in several degrees of initial stiffness. The bending moment - relative rotation of semirigid connections are governed by Kishi - Chen relation. Obtained numerical results are presented into a comparative graphical manner. Short comments and conclusions end the contribution.